EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER DAN JIGSAW DENGAN PENDEKATAN KONTEKSTUAL TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KECERDASAN MAJEMUK SISWA SMP NEGERI KOTA MADIUN - Retno H, Rosa Rosdiana; Kusmayadi, Tri Atmojo; Suyono, Suyono (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research aims to find out: (1) which one provides better mathematics learning achievement: conventional, Numbered Heads Together, or Jigsaw with contextual approach learning model, (2) which one provides better mathematics learning achievement: the students with linguistic, logical-mathematics, or interpersonal intelligence, (3) in each multiple intelligence, which one provides better mathematics learning achievement: conventional, Numbered Heads Together, or Jigsaw with contextual approach learning model, and in each learning model, which one provides better mathematics learning achievement: the students with linguistic, logical-mathematics, or interpersonal intelligence. This study was a quasi-experimental research with 3x3 factorial design. The population of this research was the seventh-year-students of State Junior High Schools of Madiun Municipality in the school year of 2012/2013 with the students of SMPN 4 Madiun, SMPN 6 Madiun, and SMPN 10 Madiun as the sample. The research instrument used was mathematics learning achievement test and questionnaire of multiple intelligence. The hypothesis test used was unbalanced two way analysis of variances. The test on the hypothesis revealed that: (1) learning model of Jigsaw with contextual approach provided better mathematics learning achievement than conventional and Numbered Heads Together learning model, while learning model of Numbered Heads Together provided better mathematics learning achievement than conventional learning model, (2) there was no difference in mathematics learning achievement between students with linguistic, logical-mathematics and interpersonal intelligence, (3) in each multiple intelligence, learning model of Jigsaw type with contextual approach provided better mathematics learning achievement than conventional and Numbered Heads Together learning model, while learning model ofÂ Numbered Heads Together provided better mathematics learning achievement than conventional learning model, and in each learning model, there was no difference in mathematics learning achievement between students with linguistic, logical-mathematics and interpersonal intelligence. Keywords: Learning Model, Jigsaw, Contextual Approach, Numbered Heads Together, Multiple Intelligence.